The Influence of Internal Motivation and Digital Literacy Towards Students’ Proactivity - Ibnu Siswanto; Mingchang Wu; Asri Widowati; Muhkamad Wakid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The Indonesian government runs Teaching Campus Program as part of the Merdeka Learning Campus Merdeka (MBKM) – Independent Campus Program – which aims to provide opportunities for students to learn and develop hard and soft skills through meaningful activities outside the classroom. Proactivity has been considered a crucial competency to support one's success and this study aims at determining the factors that affect it. The aims of this study is to analyses the effect of student’s internal motivation and digital literacy on their proactivity. This study use a quantitative method, it involved 132 students who participated in Phase 1 of the Teaching Campus Program. The data were collected using an online questionnaire. The data were analyzed by regression and the results showed that students’ internal motivation and digital literacy had a positive and significant influence on their proactivity. The result of study found that to enhance students’ proactivity, their internal motivation and digital literacy need to be put forward. To stimulate students’ internal motivation, they should be asked frequently about their learning goals and objectives in higher education, or their targets after graduation, while improving their digital literacy is by applying online learning (e-learning) in the classroom. The Massive Open Online Courses (MOOCs) learning system can also be implemented to improve digital literacy skills.